INFLUENCE OF CHARACTER EDUCATION ON POLITICAL LEADERSHIP IN ISLAM - Karimullah, Suud Sarim (Jurnal Studi Islam, 2023)
This study highlights the significant impact of character education in the Islamic context on political leadership development. This study bases its analysis on literature studies carried out in an integrative and comprehensive manner by examining and combining various relevant literature sources. The results show that character education in Islam is based on strong moral and ethical principles, including honesty, integrity, justice, and social responsibility. Political leadership in Islam puts forward the principles of justice, accountability, and concern for the general welfare. Character education is crucial in forming leaders with high morality and ethics. In addition, the influence of character education on political leadership is critical in shaping responsible, just, inclusive, and moral leaders who tend to lead sustainable leadership, maintain peace, and promote justice. In this regard, the influence of character education on political leadership in Islam is critical to creating leaders who can maintain peace, resolve conflicts, and participate in moral international diplomacy. Character education also makes leaders who can communicate honestly, maintain morality and ethics, and lead with integrity.